2014
DOI: 10.1088/0067-0049/211/2/17
|View full text |Cite
|
Sign up to set email alerts
|

The Tenth Data Release of the Sloan Digital Sky Survey: First Spectroscopic Data From the SDSS-Iii Apache Point Observatory Galactic Evolution Experiment

Abstract: The Sloan Digital Sky Survey (SDSS) has been in operation since 2000 April. This paper presents the tenth public data release (DR10) from its current incarnation, SDSS-III. This data release includes the first spectroscopic data from the Apache Point Observatory Galaxy Evolution Experiment (APOGEE), along with spectroscopic data from the Baryon Oscillation Spectroscopic Survey (BOSS) taken through 2012 July. The APOGEE instrument is a near-infrared R ∼ 22,500 300-fiber spectrograph covering 1.514-1.696 µm. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
492
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 887 publications
(501 citation statements)
references
References 75 publications
6
492
0
3
Order By: Relevance
“…Similar to the case of Bothwell et al (2014) and Bauermeister et al (2013), the stellar masses and SFRs of their samples were also obtained from the MPA-JHU group and drawn from SDSS DR10 (Ahn et al 2014). They showed that their samples correspond to star-forming galaxies at the redshift.…”
Section: Measurement Of Molecular Gas Mass From Cosupporting
confidence: 65%
“…Similar to the case of Bothwell et al (2014) and Bauermeister et al (2013), the stellar masses and SFRs of their samples were also obtained from the MPA-JHU group and drawn from SDSS DR10 (Ahn et al 2014). They showed that their samples correspond to star-forming galaxies at the redshift.…”
Section: Measurement Of Molecular Gas Mass From Cosupporting
confidence: 65%
“…Standard CCD reduction techniques (e.g., bias subtraction, flat fielding) were applied using a custom IRAF pipeline. Individual exposures were astrometrically aligned with respect to reference stars from the Sloan Digital Sky Survey (Ahn et al 2014) using SCAMP (Bertin 2006). Composite rgb images near photometric maximum and minimum are shown in Figure 3.…”
Section: Optical Observations Of the Psr J1641+8049 Systemmentioning
confidence: 99%
“…The sample of compact star-forming galaxies was selected from the spectroscopic data base of the SDSS DR7 (Abazajian et al 2009) and SDSS/BOSS DR10 (Ahn et al 2014;Dawson et al 2013;Smee et al 2013). The criteria were: 1) only galaxies with angular diameters 6 were selected to minimize the aperture corrections of the derived luminosities and stellar masses.…”
Section: The Samplementioning
confidence: 99%